Terrible triad of elbow: a case managed with radial head prosthesis - Sanikop, S. T.; Bhuti, Gangadhar; Jain, Sarthak; Chandra , Rellu Sarath (International Journal of Research in Orthopaedics, 2024)
The terrible triad of elbow consists of radial head fracture, coronoid process of ulna fracture, and posterior or posterolateral humero-ulnar joint dislocation. Favorable outcomes are expected in cases with early surgical intervention. Here we present a 48-year-old male patient with terrible triad of elbow injury following road traffic accident who underwent radial head replacement with temporary ulno-humeral transfixing K-wire. We came to a conclusion that planned and staged anatomical restoration of ligamentous and bony structures of the elbow with combative rehabilitation will give the best possible outcome.